Pedagogy of hope: The possibilities for social and personal transformation in an Academic Language and Learning curriculum - McDougall, Jenny; Holden, Helen; Danaher, Geoff (Journal of Academic Language and Learning, 2012)
This paper examines the philosophy underpinning an Academic Language and Learning (ALL) curriculum taught to enabling students at a regional Australian university. At a time when there is increasing interest in widening access to university learning as a means of meeting socio-economic objectives – and a growing scepticism about the value of such moves – this discussion provides valuable insights into an established enabling program and its approach to teaching students academic writing. We argue that the philosophy behind this ALL subject resonates with a pedagogy of hope, where “hope” may be construed as a belief that a different future is possible. Students are provided with opportunities to engage in critical dialogue about the world and themselves, and to share such thoughts in a collective forum. At one level, this means encouraging students to adopt a mode of reasoning that can appreciate the constructed nature of all knowledge forms. At another, the curriculum allows students to reflect on the ways in which their personal values and beliefs have been formed, and possibly even changed as a result of their studies. An analysis of the curriculum, using examples of student responses to illustrate key concepts, highlights a range of potential benefits for the individual, pertaining to both social responsibility and personal transformation. These findings show how the process of academic writing is linked to some of the broader aims of university learning, not all of which can be easily quantified, or justified in economic terms.